Minat Belajar Pendidikan Jasmani Pada Siswa SMP Negeri 24 Makassar - Nukhrawi Nawir (ILIN Institute Makassar, 2022)
This research is descriptive research. This research aims to obtain data regarding the level of interest in learning physical education among students at SMP Negeri 24 Makassar. The population in this study were all class VII students of SMP Negeri 24 Makassar. The sample consisted of 25 students (i) of SMP Negeri 24 Makassar. The sample from this research was taken from 25% of students (i) and was determined using random sampling. Research data collection was carried out using questionnaires or questionnaires. The research used the Validity Test and Reliability Test, this was done to find out whether it was valid or not, as well as whether the questionnaire was reliable or not which would be used as a benchmark to measure students' level of interest in participating in physical education learning using the SPSS 21.0 program. Based on the results of the instrument validity test selection carried out twice, the researcher obtained 39 valid statements and 25 invalid statements. Meanwhile, valid statements are considered capable of being a research benchmark. The explanation regarding the results of this research is that the interest in learning physical education of students at SMP Negeri 24 Makassar is in a good category. The results of collecting student questionnaire scores were found for question items that received t-scores of 4: 288, 3: 607, 2: 59, 1: 21. Based on the results obtained, it showed that the interest of students at SMP Negeri 24 Makassar in participating in physical learning was in a good category. Penelitian ini adalah penelitian deskriptif. Penelitian ini bertujuan untuk mendapatkan data mengenai tingkat minat belajar pendidikan jasmani pada siswa SMP Negeri 24 Makassar. Populasi pada penelitian ini adalah seluruh siswa kelas VII SMP Negeri 24 Makassar. Sampel terdiri dari 25 siswa(i) SMP Negeri 24 Makassar. Sampel dari penelitian ini diambil dari 25% siswa(i) dan ditemtukan menggunakan random sampling . pengumpulan data penelitian dilakukan dengan menggunakan angket atau kusioner. Penelitian menggunakan Uji Validitas dan Uji Reabilitas, hal ini dilakukan untuk mengetahui valid tidaknya, serta reliable atau tidaknya angket yang akan dijadikan tolak ukur untuk mengukur tingkat minat siswa dalam mengikuti pembelajaran pendidikan jasmani menggunakan program SPSS 21.0. Berdasarkan hasil seleksi pengujian validitas instrument dilakukan sebanyak dua kali, peneliti mendapatkan 39 pernyataan valid dan 25 pernyataan yang tidak valid. Sedangkan pernyataan valid dianggap mampu menjadi tolak ukur penelitian. Adapun penjelasan mengenai hasil dari penelitian ini adalah minat belajar pendidikan jasmani siswa SMP Negeri 24 Makassar berada dalam kategori baik. Hasil dari pengumpulan skor angket siswa ditemukan untuk butir pertanyaan yang mendapa t-skor 4 : 288, 3 : 607, 2 : 59, 1 : 21. Berdasarkan hasil yang diperoleh menunjukkan bahwa minat siswa SMP Negeri 24 Makassar dalam mengikuti pembelajaran jasmani berada pada kategori baik.